Socialization of the Use of Prime, Odd & Even Number Calculation Applications using Visual Basic 6.0 - Nurlista Iryanti; Novita Sari; Nyimas Aulia; Akhmad Sayuti (Generasi Sains Indonesia, 2025)
The socialization of Visual Basic 6.0 based applications for calculating prime, odd and even numbers aims to introduce efficient tools for studying and implementing basic mathematical concepts interactively. This application is designed with a user-friendly interface to support mathematics teaching, both at secondary school level and in basic programming training activities. The app's key features include: Prime Number Check: Allows users to identify whether a number is a prime number. Odd and Even Classification: Provides a feature that automatically determines whether a certain number is odd or even. Calculations in a Specific Range: Provides calculation results for numbers within a specified range, supporting the exploration of mathematical patterns. The socialization process is carried out through training and interactive demos for potential users, such as teachers, students and the technology community. Evaluation shows that this application is able to improve understanding of basic mathematical concepts and speed up the manual calculation process. By utilizing Visual Basic 6.0 as a development platform, this application offers flexibility and compatibility with older operating systems, making it accessible to users with limited hardware. It is hoped that this application can be a useful educational tool in studying mathematics practically.